Black Box Attack of Simulation Secret Key using Neural-Identifier: هجوم الصندوق الأسود لمحاكاة أنظمة التشفير الانسيابي باستخدام المعرف العصبي - Khaled M. Alalayah - Khadija M. H. Alaidarous - Ibrahim M. G. Alwayle - Ahmed A. Alattab (Journal of engineering sciences and information technology, 2019)
The issue of the cryptanalysis is defined as the unknown issue or problem related to the identification of the system where the major goal of the cryptanalysis is for the design of the system for various steps involved. Neural networks will be ideal tool for Black-Box system identification. The black-Box attacks against secret key cryptosystems (stream cipher system) would be presented by considering a Black-Box Neuro-Identifier model to retain two different objectives: first is for finding out the key from the provided plaintext-cipher to pair, while the second objective is to emulator construction a neuro-model for the target cipher system. There are many researches going on considering the various models of encryption where ANN is being used as single layered or multi layered perceptron. The above defined cryptographic techniques are sometimes also termed as the Neural Cryptography. As the ANN model relies on the feedforward working criteria means it can be used for the generation of some effective and efficient encryption methodologies. Cryptanalysis is considered as significant footstep for evaluating and checking quality of any cryptosystem. A portion of these cryptosystem guarantees secrecy and security of huge data trade from source to goal utilizing symmetric key cryptography. The cryptanalyst researches the quality and distinguishes the shortcoming of the key just as enciphering calculation. With the expansion in key size, the time and exertion required anticipating the right key increments. These systems for cryptanalysis are changing radically to decrease cryptographic multifaceted nature. In this paper a point by point study has been directed. Much cryptography strategies are accessible which depend on number hypothesis however it has the hindrance of necessity a substantial computational power, unpredictability and time utilization. To defeat these disadvantages, artificial neural networks (ANNs) have been connected to take care of numerous issues. The ANNs have numerous qualities, for example, learning, speculation, less information necessity, quick calculation, simplicity of usage, and programming and equipment accessibility, which make it exceptionally alluring for some applications. This paper gives a cutting-edge survey on the utilization of counterfeit neural systems in cryptography and concentrates their execution on estimation issues identified with cryptography.